Asuhan Kebidanan Komprehensif Pada Ibu Hamil Keputihan Dan Nyeri Perut Dengan Penerapan Asuhan Kebidanan Komplementer Terintegrasi - Wulandari, Hani; Nilawati, Iin; Elly, Nur (Gayaku Publisher, 2022)
Continuity of Care (COC) midwifery care is continuous midwifery care from pregnancy to family planning as an effort to reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). ANC has been carried out according to standards both in quantity and quality and the problem of vaginal discharge and abdominal pain is resolved with Continuity Of Care (COC) and complementary care. The implementation of the care given to Mrs.